From folds to faults: an insightful talk on structural geology - Idrus, Juliana; Hashim, Khairul Afinawati; Ismail, Mohd Khairul Azhar; Osman, Nur Masyitah (Unit Penerbitan FKAPP, 2025)
On Wednesday, 12 June 2024, a Technical Talk on Structural Geology was successfully held at Dewan Kuliah Hotel B, UiTM Cawangan Pulau Pinang, from 9.00 AM to 1.00 PM. The event was organized by the Geology (ECG253) lecturers and featured a guest speaker, Ts. Hj. Mohd Mustaqim bin Mohd Nordin, a Council Member of the Society for Engineering Geology and Rock Mechanics Malaysia (SEGRM). With his extensive knowledge and experience, the speaker delivered an enriching session that captivated the audience. The talk was specially arranged for all Part 2 students of CEEC110 (Diploma in Civil Engineering) who are currently enrolled in the ECG253 subject. It aimed to enhance their understanding of fundamental structural geology topics such as rock deformation, stress-strain relationships, fault and fold mechanics, and the critical role of geology in engineering and geotechnical applications.